2017
DOI: 10.3899/jrheum.161270
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Serious Infection in Patients with Rheumatoid Arthritis Treated with Biologics and Denosumab Observed in a Clinical Setting

Abstract: Objective.Previous studies combining biologic disease-modifying antirheumatic drugs (bDMARD) to treat rheumatoid arthritis (RA) have shown an increased risk of infection. However, the risk of infection with concurrent use of denosumab, a biologic agent for the treatment of osteoporosis, and a bDMARD remains unclear. Here, we evaluated the incidence of serious and opportunistic infections in patients treated concurrently with denosumab and a bDMARD and patients treated with a bDMARD alone.Methods.A chart review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 18 publications
(22 reference statements)
0
17
0
1
Order By: Relevance
“…41 In a chart review of 308 patients with rheumatoid arthritis in two Canadian rheumatology practices, there was a low risk of serious and opportunistic infections in patients with rheumatoid arthritis and in patients treated with denosumab plus another biologic. 42 Taken as a whole, recognizing the limitations of these studies, there is no convincing evidence for increased infection risk by combining denosumab and another biologic. Large prospective randomized trials are needed to settle the issue with certainty.…”
Section: Infection Risk Combining Denosumab With Another Biologic Agentmentioning
confidence: 99%
“…41 In a chart review of 308 patients with rheumatoid arthritis in two Canadian rheumatology practices, there was a low risk of serious and opportunistic infections in patients with rheumatoid arthritis and in patients treated with denosumab plus another biologic. 42 Taken as a whole, recognizing the limitations of these studies, there is no convincing evidence for increased infection risk by combining denosumab and another biologic. Large prospective randomized trials are needed to settle the issue with certainty.…”
Section: Infection Risk Combining Denosumab With Another Biologic Agentmentioning
confidence: 99%
“…Studies of denosumab in postmenopausal osteoporosis indicate an increased risk of skin and soft tissue infections . However, no infection safety signals have been found in studies of denosumab in patients receiving concurrent immunomodulatory treatment for rheumatoid arthritis and among patients receiving concomitant chemotherapy for solid‐organ tumors …”
Section: Pharmacologic Osteoporosis Treatmentmentioning
confidence: 99%
“…However, analysis have not confirmed that this risk extends to the combination of biologic used for RA and denosumab. There is a low absolute risk of serious infection while on denosumab [32] and a recent small retrospective study reported a low risk of serious infection and opportunistic infection in patients receiving both a RA biologic and denosumab [33]. In RA patients treated with a biologic, the risk of serious infection with denosumab appears no higher than being on zoledronic acid [34].…”
Section: Concomitant Therapymentioning
confidence: 99%